Social capital and open distance e-learning: a Bourdieusian and Marxian discourse - Pitsoe, Victor J.; Letseka, Matsephe M. (Penerbit Universiti Kebangsaan Malaysia, 2016)
A growing number of social scientists have invoked the idea of social capital in the search for answers to a broadening range of questions being confronted in the wide range of social science disciplines. With this in mind, this article explores the use of social capital as theoretical lens in understanding Open Distance e-Learning (ODeL) from a Bourdieusian and Marxian perspective. We depart from the assumption that concepts of social capital, ODeL, educational outcomes and throughput rate are intimately connected. We argue that the dynamics of social capital in ODeL are not only influencing students but are also capable of changing the structure of educational outcomes, high throughput rate and social reproduction.